International review of cell and molecular biology. Volume three hundred - Jeon, Kwang W. (Waltham, MA : Academic Press, 2013)
This serial presents current advances and comprehensive reviews in cell biology--both plant and animal. Articles address structure and control of gene expression, nucleocytoplasmic interactions, control of cell development and differentiation, and cell transformation and growth.
1. New insights into mechanisms of stem cell daughter fate determination in regenerative tissues / Aiko Sada and Tudorita Tumbar -- 2. Insights into skeletal muscle development and applications in regenerative medicine / T. Tran [and three others] -- 3. Cellular and molecular biology of neuronal dystonin / Andrew Ferrier, Justin G. Boyer, and Rashmi Kothary -- 4. Kinase-kinase interaction and modulation of tau phosphorylation / Mitsuko Hashiguchi and Toshio Hashiguchi -- 5. New insights into the role of the small ubiquitin-like modifier (SUMO) in plants / Hee Jin Park and Dae-Jin Yun -- 6. Role of melatonin and its receptors in the vertebrate retina / Allan F. Wiechmann and David M. Sherry -- 7. Photoinhibition of photosystem II / Esa Tyystjarvi.
Includes bibliographical references and index.
Keywords: Cells; Molecular biology; Cytology